Korelasi Antara General Pedagogy Knowledge dan Praktek Mengajar dengan Efikasi Diri Pada Calon Guru Biologi - Maesaroh Maesaroh; Mega Elvianasti; Irdalisa Irdalisa; Husnin Nahry Yarza (Pedagogi Hayati, 2021)
This study aimed to analyze the correlation between General Pedagogy Knowledge (GPK) and teaching practice with Self Efficacy of pre-service biology teachers. One of the most essential knowledge to provide pre-service biology teachers General Pedagogy Knowledge (GPK). This knowledge is a significant component of teacher knowledge. GPK will be reflected when pre-service biology teachers practice teaching in the classroom, and they will be supported by good Self Efficacy. In this research, self-efficacy is a pre-service biology teacher's beliefs in her ability to choose the right learning strategy when teaching practice (microteaching). The research used is the descriptive correlation method with a multiple regression approach. A total of 30 pre-service biology teachers were selected as the research sample used the purposive sampling technique. The research instruments used the RPP assessment rubric, teaching practice assessment rubric and self-efficacy questionnaire. The data obtained were analyzed using SPSS 26. Based on the test results by comparing the value of r (table) using a 5% significance level of 0.453 and r (count) obtained 0.673, there is a significant correlation between General Pedagogy Knowledge and teaching practice with Self Efficacy of pre-service biology teachers. It can be concluded that mastery of General Pedagogy Knowledge and good teaching practices can increase the Self Efficacy of pre-service biology teachers.